Effects of Three Feeding Systems on Production Performance, Rumen Fermentation and Rumen Digesta Particle Structure of Beef Cattle - Liu, Y F (Asian-Australasian journal of animal sciences, 2016)
The effects of three different feeding systems on beef cattle production performance, rumen fermentation, and rumen digesta particle structure were investigated by using 18 Limousin (steers) with a similar body weight (575±10 kg) in a 80-d experiment. The animals were equally and randomly divided into three treatment groups, namely, total mixed ration group (cattle fed TMR), SI1 group (cattle fed concentrate firstly then roughage), and SI2 group (cattle fed roughage firstly then concentrate). The results showed that the average daily gain was significantly higher in cattle receiving TMR than in those receiving SI1 and SI2 (p<0.05). Consumption per kg weight gain of concentrate, silage, and combined net energy (NEmf) were significantly decreased when cattle received TMR, unlike when they received SI1 and SI2 (p<0.05), indicating that the feed efficiency of TMR was the highest. Blood urea nitrogen (BUN) was significantly decreased when cattle received TMR compared with that in cattle receiving SI1 (p<0.05), whereas there was no difference compared with that in cattle receiving SI2. Ammonia nitrogen concentration was significantly lower in cattle receiving TMR than in those receiving SI1 and SI2 (p<0.05). The rumen area of cattle that received TMR was significantly larger than that of cattle receiving SI1 (p<0.05), but there was no difference compared with that of cattle receiving SI2. Although there was no significant difference among the three feeding systems in rumen digesta particle distribution, the TMR group trended to have fewer large- and medium-sized particles and more small-sized particles than those in the SI1 and SI2 groups. In conclusion, cattle with dietary TMR showed increased weight gain and ruminal development and decreased BUN. This indicated that TMR feeding was more conducive toward improving the production performance and rumen fermentation of beef cattle